Liquid Level Process Control with Fuzzy Logic Based Embedded System - (:unkn) unknown (IEEE, 2015)
In this study, the design of embedded Sugeno fuzzy logic based controller for controlling non-linear liquid level process is realized. First, the system was activated on Matlab-Simulink platform and uploaded to Arduino Mega. With this study, activation of modern control methods on embedded systems is simplistically proven. When the control system operation was checked out, it has been observed that it was pretty successful.